In Silico Shear and Intramural Stresses are Linked to Aortic Valve Morphology in Dilated Ascending Aorta. (August 2017) - Pasta, S.; Gentile, G.; Raffa, G.M.; Bellavia, D.; Chiarello, G.; Liotta, R.; Luca, A.; Scardulla, C.; Pilato, M.
Abstract : Objective/Background: The development of ascending aortic dilatation in patients with bicuspid aortic valve (BAV) is highly variable, and this makes surgical decision strategies particularly challenging. The purpose of this study was to identify new predictors, other than the well established aortic size, that may help to stratify the risk of aortic dilatation in BAV patients. Methods: Using fluid–structure interaction analysis, both haemodynamic and structural parameters exerted on the ascending aortic wall of patients with either BAV ( n = 21) or tricuspid aortic valve (TAV; n = 13) with comparable age and aortic diameter (42.7 ± 5.3 mm for BAV and 45.4 ± 10.0 mm for TAV) were compared. BAV phenotypes were stratified according to the leaflet fusion pattern and aortic shape. Results: Systolic wall shear stress (WSS) of BAV patients was higher than TAV patients at the sinotubular junction (6.8 ± 3.3 N/m 2 for BAV and 3.9 ± 1.3 N/m 2 for TAV; p = .006) and mid-ascending aorta (9.8 ± 3.3 N/m 2 for BAV and 7.1 ± 2.3 N/m 2 for TAV; p = .040). A statistically significant difference in BAV versus TAV was also observed for the intramural stress along the ascending aorta (e.g., 2.54 × 10 5 ± 0.32 × 10 5 N/m 2 for BAV and 2.04 × 10 5 ± 0.34 × 10 5 N/m 2 for TAV; p < .001) and pressure index (0.329 ± 0.107 for BAV and 0.223 ± 0.139 for TAV; p = .030). Differences in the BAV phenotypes (i.e., BAV type 1 vs. BAV type 2) and aortopathy (i.e., isolated tubular vs. aortic root dilatations) were associated with asymmetric WSS distributions in the right anterior aortic wall and right posterior aortic wall, respectively. Conclusion: These findings suggest that valve mediated haemodynamic and structural parameters may be used to identify which regions of aortic wall are at greater stress and enable the development of a personalised approach for the diagnosis and management of aortic dilatation beyond traditional guidelines.